2006
DOI: 10.1088/0741-3335/48/12b/s02
|View full text |Cite
|
Sign up to set email alerts
|

Physics of burning plasmas in toroidal magnetic confinement devices

Abstract: Some of the crucial physics aspects of burning plasmas magnetically confined in toroidal systems are presented from the viewpoint of nonlinear dynamics. Most of the discussions specifically refer to tokamaks, but they can be readily extended to other toroidal confinement devices. Particular emphasis is devoted to fluctuation induced transport processes of mega electron volts energetic ions and charged fusion products as well as to energy and particle transports of the thermal plasma. Long time scale behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
145
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(156 citation statements)
references
References 133 publications
(200 reference statements)
11
145
0
Order By: Relevance
“…In fusion plasmas, fast ions in the MeV energy range have velocities comparable with the typical Alfvén speed. In addition, SAW group velocity is directed along the magnetic field line and, therefore, fast ions can stay in resonance and effectively exchange energy with the wave [1,2]. SAW in a nonuniform equilibrium experience collisionless dissipation (continuum damping [3,4,5]), due to singular structures that are formed where the SAW continuum is resonantly excited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fusion plasmas, fast ions in the MeV energy range have velocities comparable with the typical Alfvén speed. In addition, SAW group velocity is directed along the magnetic field line and, therefore, fast ions can stay in resonance and effectively exchange energy with the wave [1,2]. SAW in a nonuniform equilibrium experience collisionless dissipation (continuum damping [3,4,5]), due to singular structures that are formed where the SAW continuum is resonantly excited.…”
Section: Introductionmentioning
confidence: 99%
“…In tokamaks, the magnetic field intensity varies along the field line. This creates gaps in the SAW continuous spectrum [6] due to translational symmetry breaking, analogous to electrons traveling in a periodic lattice [1,2]. Two types of collective shear Alfvén instabilities exist in tokamak plasmas: energetic-particle continuum modes (EPM) [7], with frequency determined by fast particle characteristic motions, and discrete Alfvén eigenmodes (AE), with a frequency inside SAW continuum gaps [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simflar considerations can be made for other toroidal magnetized plasma equilibria, such as steUarators, or -more generally -for any general periodic modulation of the B field strength. As a consequence of this lattice symmetry breaking, frequency gaps are formed in the s.A. continuous spectrum, similar to forbidden energy bands for electrons moving in a onedimensional crystal lattice [6,8,9]. The best known example is the toroidicity induced frequency gap [17], however each equilibrium geometry modulation generates its own particular structures in the s.A. continuous spectrum [6,8,9].…”
Section: Collective Behaviors and Fast Ion Transportmentioning
confidence: 99%
“…General references on the first issue are provided by the ITER physics basis [4] and its recent update [5], while recent and sufficiently comprehensive reviews can be found in [6,7,8]. On the second issue, experimental investigation is in the very early development stage, so only fairly recent theoretical reviews are available [6,8,9].…”
Section: Introductionmentioning
confidence: 99%